2019
DOI: 10.5617/jea.6737
|View full text |Cite
|
Sign up to set email alerts
|

‘We’re Gonna Be Addressing Your Pepsi Use’

Abstract: Methadone Maintenance Treatment (MMT) in the United States has recently adopted an approach based on the principles of the Recovery movement -a view of treatment informed by addiction-as-disease models but also incorporating social, psychological, and spiritual components. Although organizations that administer drug treatment services claim that the shift represents a more client-centered, individualistic approach, it may not meet the needs of the many individuals who use MMT to reduce the harms of drug use, l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 35 publications
(45 reference statements)
0
6
0
Order By: Relevance
“…Similarly, while the Substance Abuse and Mental Health Services Administration (SAMHSA) provides treatment providers with recommendations on how to determine patient eligibility for take-home doses, clinics have wide latitude to determine which patients meet that standard. For example, some clinics will not provide any take-home doses to patients who use cannabis or drink alcohol [ 15 ]. Thus, there is substantial diversity among individual clinics in regard to how many take-home doses are allowed and under what circumstances they are provided [ 11 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, while the Substance Abuse and Mental Health Services Administration (SAMHSA) provides treatment providers with recommendations on how to determine patient eligibility for take-home doses, clinics have wide latitude to determine which patients meet that standard. For example, some clinics will not provide any take-home doses to patients who use cannabis or drink alcohol [ 15 ]. Thus, there is substantial diversity among individual clinics in regard to how many take-home doses are allowed and under what circumstances they are provided [ 11 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…For those in substance use treatment programs such as methadone maintenance treatment, like myself, the situation can be even more fraught. Arguing against a treatment provider, where the power differential between doctor and patient is even more one-sided, could potentially put one's treatment in jeopardy ( Frank, 2019 ; Strike et al, 2013 ; Caplehorn et al, 1996 ).…”
Section: Discussionmentioning
confidence: 99%
“…Methadone maintenance treatment (MMT) in the United States (U.S.), and particularly the clinic system of distribution, is often criticized as punitive, over-regulated, and misaligned to the needs of many patients ( Frank, 2018 , Frank, 2019 ; McElrath, 2018 ; Novick et al, 2015 ). However, as someone who both studies, and has been on MMT for approximately 15 years, I am hopeful that changes to the regulations that COVID-19 initially caused may have given us a chance to do it better.…”
mentioning
confidence: 99%
“…Such organizations, who argue that take-home regulations are far too restrictive, point out that previous research has linked MMT's low rates of use and retention to its time-consuming, intrusive nature ( Frank, 2018 ; Nolan et al, 2015 ; Open Society Foundation, 2010 ; Strike et al, 2013 ). Moreover, qualitative studies have demonstrated the tremendous difficulty of maintaining a job, school, or stable life while forced into a system of endless daily attendance—often early in the morning and for many hours at a time ( Frank, 2019 ; Gerra et al, 2011 ). When the threat of COVID-19 is reduced most participants who have been enjoying the benefits of expanded take-homes will not want to revert to pre-COVID-19 regulations, and forcing them to do so would almost certainly lead to increased drop-outs.…”
mentioning
confidence: 99%
See 1 more Smart Citation